2002
DOI: 10.1093/humrep/17.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Early massive follicle loss and apoptosis in heterotopically grafted newborn mouse ovaries

Abstract: The results of the present study indicate that transplantation rather than cryopreservation accounts for the major and early loss of primordial follicles in grafted newborn mouse ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
3
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(128 citation statements)
references
References 33 publications
9
111
3
5
Order By: Relevance
“…However, a majority of primordial follicles in frozen-thawed canine ovarian tissues reportedly disappears after transplantation ( Table 1). The main reason for the follicular loss after cryopreservation and xenografting seems to be the ischemic effect which takes place after transplantation rather than cryopreservation per se [16,29]. Several attempts have been The results are shown as the mean±SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a majority of primordial follicles in frozen-thawed canine ovarian tissues reportedly disappears after transplantation ( Table 1). The main reason for the follicular loss after cryopreservation and xenografting seems to be the ischemic effect which takes place after transplantation rather than cryopreservation per se [16,29]. Several attempts have been The results are shown as the mean±SD.…”
Section: Discussionmentioning
confidence: 99%
“…The main drawback of ovarian cryopreservation followed by transplantation is that a large proportion of follicles are lost during the initial ischemia which occurs after transplantation [9][10][11][12][13][14][15][16]. Therefore, reducing the damage due to the ischemic interval between transplantation and revascularization is essential to maintaining both follicular reserve and the function of the graft.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Liu et al cryopreserved primordial follicles developed to preantral follicles by in vivo grafting but were then recovered and cultured to maturity by IVM (4). The same group also found apoptosis and impaired function in frozen and thawed granulosa cells after transplantation (24). It was suggested that granulosa cells are more active metabolically than primordial oocytes and thus were more subject to ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…In sheep, autotransplantation of frozen-thawed ovarian cortex [85] and of hemi-ovaries [94] has resulted in pregnancies, deliveries and prolonged hormone production [7,8]. Nevertheless, in all these cases there was a reduction in the total follicular number due to ischemia, therefore ovarian function was transient [95]. Only eight of 80 human oocytes aspirated from a cryopreserved transplanted ovary were suitable for IVF and only one oocyte fertilized normally [96].…”
Section: Cryopreservation Of Ovarian Tissuementioning
confidence: 99%
“…The first human pregnancy by cryopreserved ovarian cortex and transplantation was recently reported [9]. It appears that the main obstacles to successful restoration of fertility from frozenthawed ovarian cortex are adhesions and the massive ischemic damage to follicles until neovascularization develops [95]. Most follicles which survive cryopreservation undergo ischemic loss during the time required for neovascularization [97].…”
Section: Cryopreservation Of Ovarian Tissuementioning
confidence: 99%